2009
DOI: 10.1126/science.1174190
|View full text |Cite
|
Sign up to set email alerts
|

Aragonite Undersaturation in the Arctic Ocean: Effects of Ocean Acidification and Sea Ice Melt

Abstract: The increase in anthropogenic carbon dioxide emissions and attendant increase in ocean acidification and sea ice melt act together to decrease the saturation state of calcium carbonate in the Canada Basin of the Arctic Ocean. In 2008, surface waters were undersaturated with respect to aragonite, a relatively soluble form of calcium carbonate found in plankton and invertebrates. Undersaturation was found to be a direct consequence of the recent extensive melting of sea ice in the Canada Basin. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
241
2
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 305 publications
(264 citation statements)
references
References 26 publications
8
241
2
3
Order By: Relevance
“…These low saturation zones will be associated with increased melting of ice and freshwater inputs leading to a decrease in total alkalinity [7]. Undersaturated conditions have already been found in near coastal waters under the influence of heavy freshwater influence [38]. Temperate latitudes showed large absolute changes in V a , in the Atlantic (site 4, from V a ¼ 3.7 in 1860 to V a ¼ 1.9 in 2095) as well as in the Pacific (site 9, from V a ¼ 3.6 in 1860 to V a ¼ 1.7 in 2095).…”
Section: Discussionmentioning
confidence: 99%
“…These low saturation zones will be associated with increased melting of ice and freshwater inputs leading to a decrease in total alkalinity [7]. Undersaturated conditions have already been found in near coastal waters under the influence of heavy freshwater influence [38]. Temperate latitudes showed large absolute changes in V a , in the Atlantic (site 4, from V a ¼ 3.7 in 1860 to V a ¼ 1.9 in 2095) as well as in the Pacific (site 9, from V a ¼ 3.6 in 1860 to V a ¼ 1.7 in 2095).…”
Section: Discussionmentioning
confidence: 99%
“…In surface waters, is lower in cold, high-latitude oceans than in tropical and temperate oceans because of increased CO 2 solubility, the sensitivity of acid-base dissociation coefficients at cold temperatures, and ocean mixing patterns. Although surface waters in high-latitude oceans today are generally supersaturated with respect to aragonite (aragonite is more soluble than calcite), recent studies have reported undersaturated seawater in the Canada Basin of the Arctic Ocean (Yamamoto-Kawai et al, 2009;Bates et al, 2009). From the modeling projections, small regions of surface water in the Arctic Ocean may already be undersaturated with respect to aragonite (Gangstø et al, 2008) or will become undersaturated within a decade under the A2 Scenario of the Special Report on Emissions Scenarios (SRES-A2) (Steinacher et al, 2009;Frölicher and Joos, 2010).…”
Section: A Yamamoto Et Al: Impact Of Rapid Sea-ice Reduction In Thementioning
confidence: 99%
“…Model calculations (Orr et al 2005) indicate that a decrease in carbonate mineral saturation states is occurring throughout the global open ocean and will impact the polar oceans first (Orr et al 2005). During the summer of 2008, the Canada Basin of the Arctic Ocean was undersaturated with respect to aragonite (Yamamoto-Kawai et al 2009). …”
Section: Current Trends In Open-ocean and Coastal Phmentioning
confidence: 99%